Un documento ‘inedito’ della prima metà del IX secolo dal dossier di Ragimberga e Pietro di Niviano - Tomasini, Andrea (Scrineum, 2026)
An unpublished exchange document, dating back to the first half of the 9th century and related to the more extensive and studied dossier of Peter of Niviano, the sculdassius, has been found in the rich archive of St. Antonino of Piacenza. Through the edition of this newly identified charter, involving Raginulf, father of Ragimberga, it is possible to reconstruct the continuity of land strategies and the creation of a social network that preceded the appearance of Peter of Niviano. Furthermore, the inclusion in the dossier of other 10th-century private charters that had not been considered until now, highlights women’s central role in property transmission and social advancement within the local elite.